Training an infectious disease unit in palliative care during and post COVID-19: a qualitative longitudinal study - Alquati, Sara; Artioli, Giovanna; Martucci, Gianfranco; Tanzi, Silvia (Frontiers in Public Health, 2024)
Background To understand palliative care needs and their changes perceived by health professionals (HPs) of the Infectious Diseases Unit who participated in palliative care (PC) intensive training during the pandemic and behind/during the pandemic and one year after the outbreak. Methods A longitudinal qualitative study. Thematic analysis and meaning shift were two months after training to one year. This specific thematic approach enabled the researchers to fully understand the experiences of the HPs after they participated in the intensive PC training program during the pandemic. Participant validation meeting with the ward’s staff one year after the end of the course was performed. The two last validation meetings were used as a triangulation source to plan the new education projects. Results From March 9 to 28, 2020, the Palliative Care Services (PCS) developed intensive experiential training. Thirty-one HPs of the Infectious Diseases Unit (physicians and nurses) who were facing the COVID-19 emergency participated in the training. We conducted eight semi-structured interviews with HPs who participated in intensive training during the first wave of the pandemic (T0), two months (T1) after training and after one year (T2), during the second wave. Two validation meetings were performed as suggested by the best practices in medical education. Twenty-two infectious disease staff members participated, 8 physicians and 14 nurses. Our data show a meaning shift on five overarching themes (defined within the sub-themes): (1) Recognizing patients’ palliative care needs; (2) Responses to palliative care needs; (3) Increasing attention to intervention and care choices; (4) The suffering of health professionals; (5) Training evaluations and future expectations. At the end of Pandemic period, new training needs and acquisition have emerged. Palliative care needs changed over time: the COVID-19 themes are now far from their perception, and somehow the skills acquired during the intensive training are less present. Conclusion The pandemic led to a rapid acquisition of competencies and changes in the professionals’ behaviors, maintenance of professionals’ knowledge and competencies at two months and one year. COVID has improved relationships and increased interactions with the infectious world but that it has not been enough. The integration between PC and Infectious world needs models of integration to implement.